La Satisfaction Dans Les Études : Validation De L’échelle De Vallerand Et Bissonnette (1990) Et Son Impact Sur Le Travail Scolaire Perçu Des Lycéens - Bawa Ibn Habib; Moumoula Issa Abdou (European Scientific Journal, ESJ, 2018)
This study not only attempts to validate a cross-cultural measure of satisfaction in Canadian-inspired high school studies among Togolese students, but also to ascertain the effects of academic satisfaction on their perception of their school work. To achieve this double objective, 644 high school students have agreed to participate in the survey and to appreciate their school work. The results relating to the psychometric properties of the scale support those obtained by the authors during its construction. In addition, school satisfaction has been foundational in the psychogenetic understanding of school work.